Stopping Power for Tungsten - Adwan N. H. Al-Ajili; Sabah M. Aman Allah; Rafa A. Abad; Ahmad M. O. Al-Bayti (Tikrit Journal of Pure Science, 2023)
In this paper we report the values of radiative, collisional and total stopping power of electrons (β-) for Tungsten element by using Bethe-Bloch relativistic formula. All related equations were inputted into MathCad2012 using the ionization potential value for Tungsten in the energy range (0.1 - 10) MeV. The results show that the collisional stopping power dominates radiative stopping power. This is in excellent agreement with the values of Estar in the energy range (0.01 – 3) MeV, but at energy levels greater than 3 MeV the Bethe-Bloch relativistic formula requires some corrections to minimize errors in results.